Genetic tests aid in counseling of fetuses with cerebellar vermis defects. (28th May 2020) - Li, Lushan; Fu, Fang; Li, Ru; Xiao, Weiqiang; Yu, Qiuxia; Wang, Dan; Jing, Xiangyi; Zhang, Yongning; Yang, Xin; Pan, Min; Liu, Zequn; Liao, Can
Abstract: Objective: To assess the value of chromosome microarray analysis (CMA) and whole exome sequencing (WES) in fetuses with cerebellar vermis defects (CVD). Methods: From 2013 to 2019, we performed CMA on 43 fetuses with CVD, who were divided into cerebellar vermis hypoplasia (CVH) group and Dandy‐Walker malformation (DWM) group according to morphological subtypes. Subsequently, WES was performed on 19 fetuses with normal CMA results to identify diagnostic genetic variants (DGVs). Results: Chromosome aneuploidies and clinically significant copy number variants were identified in 23.3% (10/43) of fetuses, and a significantly higher positive rate was found in fetuses with multiple compared with isolated malformations (36% vs 5.6%, P = .028). STAG2 genes related to Xq25 duplication syndrome was possibly a novel candidate gene for CVD. WES detected eight DGVs in seven genes among the 19 fetuses tested. Autosomal recessive ciliopathies (4/8) caused by TMEM231, CSPP1, and CEP290 mutations, were the most frequent monogenetic diseases, followed by Opitz GBBB syndrome (2/8) caused by MID1 and SPECC1L variants. Conclusion: The combined use of CMA and WES has the potential to provide genetic diagnoses in 42% (18/43) of fetal CVD. WES should be offered when CMA results are normal.